The ability to meet 2100-calorie intake to identify economic gap in Rimbang Baling - Yurna Nudesia Anggun; Ario Digdo Akbar; Cahyono Topan; Wijayanto Agustinus (BIO Web of Conferences)
Bukit Rimbang Bukit Baling landscape in Riau is not only a habitat for the Sumatran tigers but also for indigenous people who have resided the area for centuries. These communities highly depend on the landscape for livelihood, with 94.1% engaged in rubber farming and non - timber forest product (NTFP) harvesting. Landscape designation as a Wildlife Reserve has been limiting the communities' activities. The remote condition, coupled with the decline in global rubber prices, has further increased the vulnerability of these communities to poverty. This study aims to provide an in-depth analysis of the welfare of the six villages adjacent and within the reserve by estimating the ability to meet the 2100-calorie intake threshold as one of indicators in calculating the poverty line, compared to the communities’ monthly income. Field observation and secondary data involving 604 community members were analyzed using descriptive methods. The study found that income from rubber alone covers only 20.27% (425.67 kcal) of the daily calorie requirement, possibly increasing to 28.51% (598.71 kcal) for those who received government subsidies. This condition led communities to engage in activities to meet calorie needs and supplement income, such as NTFP harvesting, fishing, gardening, and potentially, unlawful activities like subsistence logging and wildlife hunting.